1972
DOI: 10.1073/pnas.69.5.1282
|View full text |Cite
|
Sign up to set email alerts
|

Location of Ribosomal Protein Binding Sites on 16S Ribosomal RNA

Abstract: The distribution of ribosomal protein binding sites on the 16S ribosomal RNA molecule has been analyzed by limited ribonuclease hydrolysis of RNA-protein complexes, as well as by the interaction of individual proteins with RNA fragments purified from partial enzymatic digests. Of the six 30S subunit proteins known to interact directly with 16S RNA, proteins S4, S8, S15, S20, and, probably, S13 bind within a fragment produced by T1 RNase (12S RNA) that comprises some 900 nucleotides and covers almost the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 14 publications
(10 reference statements)
5
50
0
Order By: Relevance
“…The former confirmed the earlier heterologous binding result for S4 [4]. Given the complexities of the RNA binding sites for S4 [7,13,171 and L24 [ 14,151 , these results probably reflect a high degree of conservation of RNA sequence, and, indeed for 16 S RNA of Proteus vulgaris this has been indicated [25]. Undoubtedly, therefore, these bacterial RNA's are the best candidates for further structural investigations of protein-RNA interactions.…”
Section: Resultssupporting
confidence: 81%
“…The former confirmed the earlier heterologous binding result for S4 [4]. Given the complexities of the RNA binding sites for S4 [7,13,171 and L24 [ 14,151 , these results probably reflect a high degree of conservation of RNA sequence, and, indeed for 16 S RNA of Proteus vulgaris this has been indicated [25]. Undoubtedly, therefore, these bacterial RNA's are the best candidates for further structural investigations of protein-RNA interactions.…”
Section: Resultssupporting
confidence: 81%
“…The sites on the 16 S RNA to which certain proteins from the 30 S ribosomal particle become attached have been localised within the primary sequence of the RNA [6,7]. This was done by binding the proteins to specific fragments of the RNA [6] or by isolating regions of the RNA protected against nuclease digestion by the presence of a protein [7]. Analogous studies of some components of the 50 S ribosomal particle have revealed that three proteins participate in binding the 5 S RNA to a region somewhere within the 3'-two-thirds of the 23 S RNA [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some progress has been made in this direction recently. The sites on the 16 S RNA to which certain proteins from the 30 S ribosomal particle become attached have been localised within the primary sequence of the RNA [6,7]. This was done by binding the proteins to specific fragments of the RNA [6] or by isolating regions of the RNA protected against nuclease digestion by the presence of a protein [7].…”
Section: Introductionmentioning
confidence: 99%
“…The protein chains of many mutant S4 proteins are shorter or longer than wild type S4; b) Protein S4 binds specifically to E. coli 181 and the protein-RNA interaction has been studied in some detail [14,15,17,18].…”
Section: Introductionmentioning
confidence: 99%